217k views
5 votes
Simplify. Consider all cases.

f

14−(6−x)
(14-(6-x) is surround by two absolute bars)

1 Answer

4 votes

Explanation:

As (14-(6-x) is surrounded by two absolute bars.

so


\left|14-\left(6-x\right)\right|

Expanding
14-\left(6-x\right)


=14-6+x


\mathrm{Subtract\:the\:numbers:}\:14-6=8


=x+8

so


=\left|x+8\right|

Thus


\left|14-\left(6-x\right)\right|=\left|x+8\right|

It can also be solved by x, such as


\left|x+8\right|=0


\mathrm{Apply\:absolute\:rule}:\quad \mathrm{If}\:|u|\:=\:0\:\mathrm{then}\:u\:=\:0


x=-8

User Darshan P
by
5.6k points